'You see, it's sort of tricky for the L2-user': the puzzle of idiomaticity in English as a lingua franca - Prodromou, Luke (2005)
Much has been claimed recently for the role of idiomaticity in L1 acquisition and fluency and many of these insights have been applied, in my view, uncritically in many cases, to the context of L2 use. Until recently, very little attempt was made to test out the applicability of these insights to English as a Lingua Franca by examining naturally-occurring L2 discourse. This thesis sets out to explore the reasons why even successful L2-users may find the phenomenon of idiomaticity difficult. It investigates the apparent paradox between idiomaticity in L1 use and L2 use, whereby for the L1-user, idiomaticity, in all its guises, makes for ease of processing and the promotion of fluency while in L2 use it seems, in some of its manifestations at least, to be error- prone and elusive. Drawing on an original corpus of spoken English as a Lingua Franca, I apply a combination of corpus techniques and techniques of discourse analysis within a sociocultural framework in order to identify the underlying factors that differentiate L1 and L2 idiomaticity. I illustrate the argument by looking at two different manifestations of idiomaticity: ‘minimal’ units of idiomaticity (two word phrases) and more traditional ‘colourful’ idioms. The results suggest that L2-users avoid or have difficulty with ‘native-like’ idiomaticity because L1 idiomaticity involves more than formulaic sequences of greater or lesser semantic opacity; it is a more extended and diffuse phenomenon that generates subtle webs of semantic, pragmatic and discourse prosodies. It is through these situated webs of signification that L1-users achieve fluency and the promotion of self rather than in the manipulation of isolated idiomatic units in vacuo. Note: When I use the terms ‘native’ and ‘non-native’ I put them in inverted commas to indicate to the reader that I do not subscribe to the deficit view of L2 use that these terms are often associated with. My preferred terms are ‘L1-user’ and ‘L2-user’ (Cook, 2002).